Safety of intraoperative autologous plasma incubation of corneal grafts for reducing endothelial cell loss: a pilot study - Mercado, Carolina; Hernández, Cesar; Lopez-Rojas, Carolina; De La Sen-Corcuera, Borja; Anitua, Eduardo; Barraquer, José Ignacio; Gutiérrez, Angela; Otero, Ernesto; Sabater, Alfonso L. (Frontiers in Medicine, 2024)
Background/aims Corneal endothelial cell loss contributes to transplant failure. Autologous plasma products (APP) activate salvaging pathways that can prevent oxidative stress perioperatively. This study aimed to evaluate the safety of intraoperative incubation of full-thickness corneal grafts in platelet-rich plasma (aPRP) and plasma rich in growth factors (PRGF-Endoret) in mitigating postoperative corneal endothelial cell loss (ECL). Methods Pilot study including patients undergoing penetrating keratoplasty (PK) for various indications between June 2021 and December 2022. Patients were randomly assigned to receive either aPRP or PRGF-Endoret incubation, while those who declined intervention served as the control group. Demographic and clinical data were collected, including preoperative and postoperative endothelial cell count, intraocular pressure, pachymetry, and adverse reactions. Results Thirty individuals who underwent PK completed follow-up: eight from the aPRP group, 10 from the PRGF-Endoret group, and 12 from the control group. No adverse events related to APP treatment were recorded. In the first and third postoperative months, the APP group had significantly lower ECL percentages (37% vs. 25%, p = 0.02, and 44% vs. 33%, p = 0.02, respectively); this trend was maintained in the sixth month. When stratified, the PRGF-Endoret group showed significant differences in ECL reduction compared to controls at both time points (p = 0.03 and p = 0.05, respectively). The aPRP group showed a similar statistically significant outcome exclusively on the third postoperative month (p = 0.04). APP tended to reduce corneal edema faster than controls. Hexagonality was significantly better in the APP groups in the first and third months, particularly in the PRGF-Endoret group (p < 0.005). Conclusion Preoperative incubation with APP is safe and promotes better endothelial cell quality and quantity in the early postoperative period following PK. These findings suggest a potential clinical benefit in enhancing graft outcomes and warrant further investigation.